2000
DOI: 10.1103/physrevlett.84.250
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of Many-Electron Correlations in Photoionization of theKShell ofN2

Abstract: It is demonstrated theoretically in the random phase approximation (RPA) that due to the intershell many-electron correlations the sigma(*) shape resonance in the photoionization of K shells of the N2 molecule appears not only in the 1sigma(g)-->varepsilonsigma(u) channel as it was believed earlier on the basis of single particle calculations, but in both 1sigma(g)-->varepsilonsigma(u) and 1sigma(u)-->varepsilonsigma(g) channels. As a confirmation of this phenomenon we show that the experimental angular distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
71
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 15 publications
11
71
0
Order By: Relevance
“…Electron angular distributions for molecules fixed in space by detection of the molecular fragments have been first performed by Shigemasa and coworkers with traditional analyzers for electrons and ions (Shigemasa et al 1995) (see also Shigemasa et al (1998); Watanabe et al (1997); Cherepkov et al (2000); Cherepkov et al (2000a); Ito et al (2000); Ito et al (2000a); Motoki et al (2002) for later experiments by this group). One other group has combined timeof-flight electron spectrometers (Golovin et al 1997;Heiser et al 1997;Gessner et al 2002) with imaging of the molecular fragments.…”
Section: Photoionisation Of Fixed-in-space Moleculesmentioning
confidence: 99%
“…Electron angular distributions for molecules fixed in space by detection of the molecular fragments have been first performed by Shigemasa and coworkers with traditional analyzers for electrons and ions (Shigemasa et al 1995) (see also Shigemasa et al (1998); Watanabe et al (1997); Cherepkov et al (2000); Cherepkov et al (2000a); Ito et al (2000); Ito et al (2000a); Motoki et al (2002) for later experiments by this group). One other group has combined timeof-flight electron spectrometers (Golovin et al 1997;Heiser et al 1997;Gessner et al 2002) with imaging of the molecular fragments.…”
Section: Photoionisation Of Fixed-in-space Moleculesmentioning
confidence: 99%
“…On the other hand, those for CO are asymmetric [2,3,5,8], due to the asymmetric nature of the hetero-nuclear diatom. Calculations employing Hartree-Fock and random-phase-approximation methods and an extension of the standard multiple scattering approach reproduce key features of the measured MF-PADs well [4,7,10].…”
mentioning
confidence: 97%
“…symmetry through a plane perpendicular to the molecular axis [1,4,6,7], even if the photoemission is related to asymmetric N + -N ++ fragmentation [6]. On the other hand, those for CO are asymmetric [2,3,5,8], due to the asymmetric nature of the hetero-nuclear diatom.…”
mentioning
confidence: 99%
“…Measurement of the N1s photoelectron spectrum of N 2 as a function of photon energy distinguished the gerade and ungerade components and followed the cross sections for each component separately [61]. A later study confirmed that the shape resonance has σ u symmetry and couples primarily to the σ g channel, but inter-channel coupling leads to resonant behavior even in the σ u channel [62]. The intensity increase in the Auger spectrum at 420 eV reflects the increase in ionization cross section due to the shape resonance affecting the photoelectron channel.…”
Section: Above Threshold Resonancesmentioning
confidence: 80%